THE MULTIDISCIPLINARY LOOK AT THE ONCOLOGICAL PATIENT: PALLIATIVE CARE, SPIRITUALITY AND BIOETHICS - José Monteiro da Costa, Marcelo (Health and Society, 2023)
A multidisciplinary approach, which includes other professionals in the health area, not only the doctor, but also: the nurse, the psychologist, social worker, the religious agent ... With this look, provides a comprehensive development to the cancer patient, and in special, with palliative care, spirituality and bioethics. For the construction of this monographic work, some authors were researched, each showing their point of view. It is a multidisciplinary study, a knowledge and a holistic practice on several approaches: philosophical, anthropological, ethical, bioethical, cultural, social, psychological, theological, oncológico and among other knowledge. Having this broader look, the oncological psychologist (or any other health professional) does not tend to fall in the reductionisms in the treatment with the cancer. The objective is to point the multidisciplinary look, having a better resolution and integration in the therapy. The present research has its own characteristics of a bibliographic study, reports of experience of authors and manuals, that debate about the subject. Some articles of the period 2006 - 2022 were searched, which show subjects related to the subject.